Flow of hybrid nanofluid across a permeable longitudinal moving fin along with thermal radiation and natural convection - Gireesha, B. J.; Sowmya, G.; Khan, M. Ijaz; Öztop, Hakan Fehmi (Elsevier Ireland Ltd, 2020)
Background: The numerical investigation of nanoparticles embedded water based hybrid nanoliquid flow over porous longitudinal fin moving with constant velocity is carried out together with thermal radiation and natural convection condition. Darcy's model is implemented for the flow behaviour. The two types of boundary conditions are considered at the tip i.e., insulated tip fin and fin with known convective condition. Method: The modelled ordinary differential equation is non-dimensionalized and tackled mathematically by applying RKF (Runge Kutta Fehlberg) technique. Results: The parametric evaluation is carried out through graphs and interpreted physically. From obtained outcomes, it is noticed that, fin with known convective coefficient at the tip shows greater heat transfer rate than fin with insulated tip. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Hybrid nanofluid; Moving fin; Insulated tip; Convective tip; Thermal radiation; Natural convection